Spiritualitas Cyberspace; Interplay Post Sains-Teknologi dengan Spiritualitas Sains Dakwah - Wahyudin, Aep (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
As a product of information technology, cyberspace has brought about radical changes in all aspect of humanity, including those aspects of spirituality and religiosity. Notwithstanding of some benefits for spirituality, cyberspace has in fact been resulting in some spiritual paradoxes. Cyberspace has paradoxically functioned either as a religious communication medium or as a religion itself; either as a channel of spiritual energy or as a spirituality itself. Indeed, cyberspace is full of spiritual paradoxes: reality versus fantasy, body versus soul, and God versus man.